Assessing Urban Development Impacts in the Padang Coastline City, West Sumatra Indonesia; Coastline Changes and Coastal Vulnerability - Ulung Jantama Wisha; Ruzana Dhiauddin; Koko Ondara; Wisnu Arya Gemilang; Guntur Adhi Rahmawan (Department of Urban and Regional Planning, Diponegoro University, 2022)
The capital coastline city of Padang is intensively developed to enhance tourism attractions and protect the coastline from natural hazards and disasters. Massive urban developments applied in the coastal area have not gone well, and several regions have been eroded and unstable. This study aimed to determine the significant change in Padang city's coastline due to rapid urban development in the coastal area. Spatial analyses are employed to determine the coastline changes and coastal vulnerability, such as a DSAS (Digital Shoreline Analysis System) and Smartline-associated CVI (coastal vulnerability index) approach. A hydrodynamic and coastal model is also used to illustrate the transport mechanism and predict the level of abrasion. The result shows that substantial coastal changes and vulnerability have occurred. Of particular concern, 66 % of Padang's coastline is eroded with a rate of 0.21 - 49.4 m/year, 1% stable, and the rest, 34% experiencing accretion. More than 9% of coastal areas are categorized as highly vulnerable. The numerical model confirms the abrasion in several significant areas in Padang City, proven by the relatively high value of bed-level change (ranging from 0.39 up to -4 m) and considerable variability of seasonal sediment transport and suspended materials. The erratic hydrodynamics and ineffective coastal building are the primary factors triggering Padang City's coastal instability.